(Un)Natural Disasters: Electoral Cycles in Disaster Relief. (June 2022) - Cooperman, Alicia
Emergency spending is often exempt from campaign period restrictions and procurement guidelines, making it attractive for opportunistic politicians, but natural disasters are seen as outside political business cycles. However, droughts are frequent but challenging to measure, so politicians can leverage discretion for electoral gain. This paper analyzes electoral cycles, term limits, and partisan targeting around municipal drought declaration in Northeast Brazil. Two sources of exogeneity (rainfall shocks, electoral calendar) isolate the effect of non-climatic factors on drought declarations. I find that drought declarations, which trigger relief, are more likely in mayoral election years. Incumbents are more likely to win re-election if they declare a drought in the election year, during below or even above average rainfall. The results are consistent with interviews suggesting voters reward competent mayors and mayors trade relief for votes. This study highlights the interaction between distributive and environmental politics, which has increasing consequences due to climate change.